Analisis Kovariat bagi Data Kemortalan Bayi - Ibrahim, Noor Akma; Daud, Isa (Universiti Putra Malaysia Press, 1997)
This paper analyses the effect of various covariates on infant mortality. It uses the method for the analysis of grouped life-time in competing risks. With this approach, advantage is taken of the probability of an individual with a particular covariate failing in an interval to consolidate the significance of that covariate model.